QRIS adoption and its implications for MSME business performance: A case study of Taman Bojana Kudus - Muhammad Fatichul Falach; Musa Yahuza Danhausa (PT Bina Perfidia Akademia, 2026)
The adoption of the Quick Response Code Indonesian Standard (QRIS) among MSMEs has continued to increase; however, most studies have focused on adoption rates or income effects, leaving limited understanding of how QRIS creates business value through improved business performance. This study aims to analyze the QRIS adoption process and its implications for MSME business performance at Taman Bojana Kudus. A qualitative case study approach was employed through interviews, observations, and documentation involving three MSME owners and two consumers selected using purposive sampling. Data were analyzed using the Miles, Huberman, and Saldaña interactive model. The findings reveal that QRIS adoption is driven by perceived benefits, changing consumer preferences, and operational efficiency needs. QRIS improves transaction efficiency, service quality, consumer convenience, and business competitiveness, thereby contributing to gradual improvements in business performance. This study contributes to the digital payment literature by explaining the mechanism of business value creation through QRIS implementation among MSMEs. Abstrak Adopsi Quick Response Code Indonesian Standard (QRIS) pada UMKM terus meningkat, tetapi sebagian besar penelitian masih berfokus pada tingkat adopsi atau pengaruhnya terhadap pendapatan, sehingga mekanisme QRIS dalam menciptakan nilai bisnis melalui peningkatan kinerja usaha masih relatif terbatas dikaji. Penelitian ini bertujuan untuk menganalisis proses adopsi QRIS serta implikasinya terhadap kinerja usaha UMKM di Taman Bojana Kudus. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus melalui wawancara, observasi, dan dokumentasi terhadap tiga pelaku UMKM dan dua konsumen yang dipilih menggunakan purposive sampling. Data dianalisis menggunakan model interaktif Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa adopsi QRIS didorong oleh persepsi manfaat, perubahan preferensi konsumen, dan kebutuhan akan efisiensi operasional. Penggunaan QRIS meningkatkan efisiensi transaksi, kualitas pelayanan, kenyamanan konsumen, dan daya saing usaha, sehingga secara bertahap berkontribusi terhadap peningkatan kinerja usaha. Penelitian ini berkontribusi pada kajian pembayaran digital dengan menjelaskan mekanisme penciptaan business value melalui implementasi QRIS pada UMKM.